HSP27 induced glaucomatous damage in mice of young and advanced age - Erb, Clivia; Reinehr, Sabrina; Theiss, Carsten; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2023)
Age-related diseases such as glaucoma, a leading cause of blindness, are having an upward trend due to an aging society. In glaucoma, some patients display altered antibody profiles and increased antibody titers, for example against heat shock protein 27 (HSP27). An intravitreal injection of HSP27 leads to glaucoma-like damage in rats. We now aimed to investigate if aged mice are more prone to this damage than younger ones. Hence, we intravitreally injected HSP27 into young (1-2 months) and aged (7-8 months) mice to compare glaucomatous damage. Respective age-matched controls received PBS. Not injected eyes served as naive controls. Optical coherence tomography four weeks after injection showed no changes in retinal thickness in all groups at both ages. Cell counts and RT-qPCR revealed a significant reduction in RGC numbers in HSP27 mice at both ages. Comparing aged and young HSP27 mice, no differences in Rbpms and Pou4f1 (RGCs) expression was detected, while the Tubb3 expression (neuronal cells) was significantly upregulated in aged HSP27 animals. Neither microglia/macrophages nor (resident) microglia counts revealed significant differences in HSP27 mice at both ages. Nevertheless, increased relative Iba1 and Tmem119 expression was detected in young and aged HSP27 mice. Aged HSP27 mice displayed a significantly lower Iba1 expression than young ones, whereas Cd68 levels were upregulated. A larger GFAP+ area and an upregulation of GFAP expression in HSP27 animals of both ages indicated a macrogliosis. Also, elevated Il1b and Nos2 expression levels were observed in young and aged HSP27 mice. However, only Il1b levels were upregulated when comparing 7-8 months to 1-2 months old animals. A larger HSP25+ area was seen in aged HSP27 animals, while Hspb2 expression levels were downregulated in both HSP27 groups. The aged HSP27 group displayed an upregulated Hspb2 expression compared to young mice. Furthermore, a higher optic nerve degeneration score was noted in young and aged HSP27 groups. These findings indicate that an intravitreal injection of HSP27 led to RGC loss accompanied by inflammation. Age-dependent effects (7-8 months vs. 1-2 months) were not very prominent. The results suggest a potential role of extracellular HSP27 in the development of glaucoma.